Tyrosine phosphorylation in the human duodenum. - KELLEHER, DERMOT P; SHEILS, ORLA (BMJ, 1995)
Many growth factor receptors including the epidermal growth factor receptor function through tyrosine kinase activity. The aim of this study was to examine the constitutive level of tyrosine phosphorylation in the normal duodenum and in the hyperproliferative coeliac duodenum. A flow cytometric assay was devised using monoclonal antibody to phosphorylated (but not native) tyrosine residues to determine the levels of tyrosine phosphorylation in both CD3 positive intraepithelial lymphocytes and CD3 negative epithelial cells obtained by EDTA treatment of endoscopically obtained duodenal biopsy specimens. In addition, immunohistochemistry was performed on 18 formalin fixed coeliac duodenal biopsy specimens and eight control specimens. Tyrosine phosphorylation could be detected by flow cytometry on duodenal enterocytes and this expression was up regulated by pretreatment with epidermal growth factor. Tyrosine phosphorylation decreased with progression from the villus to the crypt, however, and was virtually undetectable on crypt enterocytes. Immunohistochemistry of the coeliac duodenum showed virtually absent tyrosine phosphorylation in the crypt. Increased tyrosine phosphorylation was detected in the infiltrating T cells. In conclusion, tyrosine phosphorylation in the duodenum is confined to the non-proliferative villous epithelium and is virtually undetectable in the proliferative crypt compartment. These findings suggest that tyrosine kinase activity is not a significant factor in the regulation of crypt cell proliferation in the human duodenum either in normal subjects or in coeliac disease patients.
PUBLISHED
Keywords: Gastroentrology; Hepatology